The Multi-Business Startup. A study of challenges and considerations concerning strategy, organization, and prioritization - Alm, Jesper; Lindblad, John (My University, 2021)
Multi-business strategies among startups, as well as entrepreneurial methods combining qualitative and quantitative data analysis with experience to enable decision making, are arguably both insufficiently researched areas. This project sought to answer two research questions on these topics. First, why and how startups can pursue multi-business strategies; and second, how teams can combine qualitative and quantitative data analysis with experience and domain expertise to help to prioritize their development backlog. A case study of one Swedish startup in the healthcare industry enabled analysis of these two questions. The data collection consisted mainly of participant observation, as the two researchers worked within the studied company. The study is achieving a well-defined picture of the company and its practices through discussion with several key individuals in the company, as well as day-to-day work with business intelligence. Conducting additional semi-structured interviews enhanced reliability and mitigated potential biases. Compilation and thematic analysis of all data lead to a discussion of the research questions supported by previous literature. The study resulted in deepened insight into the problems and considerations of a multi-business startup. For example, we unearthed challenges connected to resource allocation, organizational structure, and prioritization of feature ideas. Concerning the question of combining data with experience, it became evident that all approaches (qualitative data analysis, quantitative data analysis, and experience) are necessary but need to be thoughtfully combined. Qualitative input from the user perspective seems the most challenging to incorporate, but businesses should aim to do so at all levels of the business. Combining the idea of a so-called One Metric That Matters (OMTM) with an experimental approach might help lead the focus of the firm. In conclusion, the study suggests that multi-business startups face challenges that single-idea ventures might not encounter. However, it is important to employ the ideas of traditional entrepreneurial approaches in this new setting. We propose a checklist for practitioners pursuing a multi-business strategy to help direct their analytical and strategic focus to some key tradeoffs and considerations.
Keywords: lean startup, agile, startups, data analytics, entrepreneurship, multi-business strategy